SEXUALIDADE DE ADOLESCENTES COM TRANSTORNO DO ESPECTRO AUTISTA: PERSPECTIVA DE PAIS E PROFISSIONAIS DE APOIO - Adriana Onofre Schmitz (2024)
The sexuality of adolescents with Autism Spectrum Disorder (ASD) is little studied in Brazil, which limits understanding of the phenomenon and makes it difficult to provide these young people with guidance and support in their sexual education process. The theoretical framework that supported this study was the Theory of Social Representations (TRS), which allowed investigating the social representations of sexuality in adolescents with ASD, from the perspective of guardians and support professionals from an institution that provides services to this population. Seven managers and five professionals from the collaborating institution were interviewed. Data collection was through semi-structured interviews that were recorded and transcribed for analysis. The Collective Subject Discourse (DSC) method was used for tabulation and as a result, eight DSC were created for guardians and six DSC for support professionals, which corroborate the findings in research in Brazil and abroad. As social representations (SR) are an expression of the search to make what is perceived as uncommon common and real, the DCS showed that the sexuality of people with autism is not perceived as something natural, constituent of the subject. The process of preparing SRs, both for those responsible and for support professionals, is in the anchoring phase. This leads to the need for more discussions and studies on the topic so that it can proceed to the objectification phase, and thus complete the process of constituting SR based on the experiences and reality of adolescents with autism, and thus allow the elaboration of programs and materials focused on the topic that support the practice of guidance and support for this population.